1589. Increased Detection of Diarrheal Pathogens in Hematopoietic Stem Cell Transplant Recipients Using a Multiplexed PCR Panel. (26th November 2018) - Rogers, Wesley; Westblade, Lars; Jenkins, Stephen G; Van Besien, Koen; Singh, Harjot; Soave, Rosemary; Crawford, Carl; Satlin, Michael
Abstract: Background: Diarrhea is common among hematopoietic stem cell transplant (HSCT) recipients, but the etiology is rarely identified. Multiplexed PCR may increase the detection of diarrheal pathogens, but its role has not been evaluated in this population. Methods: In June 2016, the FilmArray™ Gastrointestinal panel (GI PCR) was implemented at NewYork-Presbyterian Hospital/Weill Cornell Medical Center to diagnose infectious diarrhea, replacing stool culture and other conventional Methods. We reviewed all adult patients who received a HSCT at our center from June 2014–May 2015 (pre-GI PCR) and June 2016–March 2017 (post-GI PCR). Clostridium difficile infection was diagnosed by PCR for toxin B gene in both cohorts. Patients were followed for 1 year post-transplant. We compared the percentage of patients with an identified diarrheal pathogen, yield of testing per diarrheal episode, and number and cost of stool tests between cohorts. Results: We identified 163 HSCT recipients in the pre-GI PCR cohort and 146 in the post-GI PCR cohort. Patients had a median of two diarrheal episodes during 1-year follow-up in both cohorts. The proportion of patients with at least one identified infectious etiology of diarrhea increased from 21.5 to 34.3% after implementation of GI PCR ( P = 0.01). Only two patients (1.2%) in the pre-GI PCR cohort tested positive for a pathogen other than C. difficile, vs. 35 patients (24.0%) in the post-GI PCR cohort ( P < 0.001). Post-GI PCR, patients were most likely to have the following pathogens: C. difficile ( n = 23, 15.8%), diarrheagenic Escherichia coli ( n = 20, 13.7%), and norovirus ( n = 10, 6.8%). The percentage of diarrheal episodes for which an infectious etiology was identified increased from 11.7% (41/351) to 20.9% (74/354; P = 0.001) in the post-GI PCR period. The median number of stool tests performed per year per patient decreased from 12 (interquartile range [IQR] 7–20) to 5 (IQR 3–11; P < 0.001). Median costs of stool testing per patient during follow-up did not differ: (pre: 473, IQR 243–851) vs. (post: 425, IQR 249–956; P = 0.23). Conclusion: After introduction of GI PCR, infectious etiologies of diarrhea were identified in a higher proportion of HSCT recipients compared with traditional stool testing, without an increase in testing costs. Disclosures: L. Westblade, BioFire Diagnostics, LLC.: Research Contractor, Grant recipient. C. Crawford, Merck: Scientific Advisor and Speaker's Bureau, Consulting fee; Redhill: Speaker's Bureau, Speaker honorarium. M. Satlin, Biomerieux: Grant Investigator, Grant recipient.